HeatnBomb Bingo Media Based on PBL Learning Model for Science Learning in Grade V Elementary School - Maulida, Dewinta Arum; Wulandari, Desi (Jurnal Ilmiah Sekolah Dasar, 2024)
The introduction of Natural and Social Sciences (IPAS) concepts should be conducted through problem-based and simple game-based methods to engage students effectively. However, field observations reveal that teachers often employ complex teaching methods accompanied by heavy assignments, causing students to struggle in comprehensively understanding IPAS concepts. This study aims to develop and analyze the effectiveness of HeatnBomb Bingo media for IPAS learning in fifth-grade elementary students. The research method used is Research and Development, with fifth-grade students as the subjects. Data analysis techniques include the Kolmogorov-Smirnov test for normality, paired sample t-test to compare pre-test and post-test results, and N-Gain test to measure learning improvement. Media validation by experts indicates that HeatnBomb Bingo is highly valid, with a score of 85.93%. The paired sample t-test shows a significance value of 0.000 < 0.05, indicating a significant impact of using HeatnBomb Bingo on students' learning outcomes. The N-Gain test result of 0.5997 reflects a 59.97% improvement in learning outcomes. Thus, HeatnBomb Bingo is valid and effective for IPAS learning. The media fosters active student participation by engaging them in discussions and problem-solving activities, enhancing their conceptual understanding in a more profound and enjoyable way.